Gillette shaving systems in China. - Ng, Kuang Hong. (2008)
This Applied Research Project is a study done on Gillette’s shaving systems in China. Concurrent with China’s booming economy, the paper seeks to evaluate its attractiveness and to explore potential business opportunities that are available to Gillette.